Social media as an agent of social solidarity in Malaysia. - Ridzuan, Abdul Rauf; Bolong, Jusang; Omar, Siti Zobidah; Osman, Mohd Nizam; Abu Said, Al Mansor; Ismail, Shafinar (Universiti Sains Malaysia, 2014)
Dato' Seri Mohd Najib Bin Hj Abd Razak, under his managerial, 1Malaysia had been announced to be the main issue in the Malaysian development. The lifelong dream of Malaysia's 6th Prime Minister, Dato' Sri Mohd Najib Bin Tun Hj Abd Razak, is a united, peaceful and prosperous Malaysia, with abundant opportunities for all citizens.